1999
DOI: 10.1021/bi990361v
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of G Protein-Coupled Receptor Regulation in Antisense mRNA-Expressing Cells with Reduced Arrestin Levels

Abstract: Previous studies with overexpressing wild-type or dominant negative nonvisual arrestins have established a role for these proteins in beta2-adrenergic receptor (beta2AR) internalization, desensitization, and resensitization. To validate and extend such findings, we employed an antisense strategy to target the nonvisual arrestins, arrestin-2 and arrestin-3, and determined the associated effects on the regulation of G protein-coupled receptor (GPCR) signaling. HEK293 cells stably expressing antisense constructs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 36 publications
3
53
1
Order By: Relevance
“…Previous reports suggest that the EP4-R, but not the EP2-R, can display rapid agonist-induced desensitization due to multiple phosphorylation sites within its C-terminal sequence (42,43). Furthermore, it is suggested that this effect is attenuated in ␤-arrestin antisense-expressing cells (44). It is conceivable that the desensitization of EP2/4-Rs seen here is also due to PKA-mediated receptor phosphorylation.…”
Section: Discussionmentioning
confidence: 53%
“…Previous reports suggest that the EP4-R, but not the EP2-R, can display rapid agonist-induced desensitization due to multiple phosphorylation sites within its C-terminal sequence (42,43). Furthermore, it is suggested that this effect is attenuated in ␤-arrestin antisense-expressing cells (44). It is conceivable that the desensitization of EP2/4-Rs seen here is also due to PKA-mediated receptor phosphorylation.…”
Section: Discussionmentioning
confidence: 53%
“…Adenovirus Construction-Recombinant adenoviruses that encode ␤-galactosidase or ␤-arrestin2 or ␤-arrestin2 antisense were prepared as described previously (30,31). Briefly, ␤-galactosidase, ␤-arrestin2, or ␤-arrestin2 antisense was cloned into shuttle vector pAdTrack-CMV by using standard cloning protocols, and the shuttle vectors were recombined with pAdEasy-1, which harbors a CMV-driven green fluorescent protein, to form the viral constructs.…”
Section: Methodsmentioning
confidence: 99%
“…Arrestin2 and GRK2 were detected using the equivalent of 8.9 μg tissue per lane, arrestin3, GRK3, and GRK5 -35.7, and GRK6 -120 μg tissue per lane. Arrestins were detected with arrestin2- [75] (1:6,000) or arrestin3-specific [79] (1:700) affinity-purified rabbit polyclonal antibodies. We used rabbit polyclonal antibodies (Santa Cruz Biotechnology, Santa Cruz, CA) to quantify GRK2 (catalog # sc-562; 1:500), GRK3 (catalog # sc-563; 1:300), and GRK5 (catalog # sc-565; 1:500).…”
Section: Western Blottingmentioning
confidence: 99%
“…If the compensation for DA depletion was aimed at restoring a normal level of G protein-mediated signaling via DA receptors, a down-regulation of arrestins and GRKs in the PD brain should be expected. It is well established that reduction of the arrestin and/or GRK concentration invariably reduces GPCR desensitization and internalization and enhances G protein-mediated signaling [3,14,27,41,58,75,103]. Therefore, decreased concentrations of arrestin/GRKs in the DA-depleted basal ganglia would impede desensitization of DA receptors and help sustain the G protein-mediated signaling.…”
Section: Functional Significance Of Changes In Arrestin and Grk Exprementioning
confidence: 99%